Field test for mechanical efficiency evaluation in matching volleyball players - Laconi, P.; Melis, F.; Crisafulli, A.; Sollai, R.; Lai, C.; Concu, A. (International Journal of Sports Medicine, 1998)
Field tests were performed in 10 volleyball (VB) players (4 females and 6 males) in order to obtain an index of mechanical work efficiency (mu' = Wmec/Woxy) while athletes played a game. Wmec was the mechanical work output, obtained by means of home made video image analysis software, by summing potential, kinetic translational and kinetic rotational energies of running and jumping athletes. Woxy was the oxidative energy consumption obtained from O2 consumption (VO2) by a telemetry device (Cosmed K2) that also gave values of pulmonary ventilation (VE) and heart rate (HR). VB were studied at rest before a game (R), during attacking phases (A) and during defensive phases (D). At R were found: VE = 11 +/- 1 l x min(-1), HR = 78 +/- 7b x min(-1), VO2 = 3.71 +/- 1.1 ml x kg(-1) x min(-1), Woxy = 75.1 +/- 22.3 J x kg(-1) x min(-1). During A all variables increased: VE = 49 +/- 6l x min(-1), HR = 149 +/- 15 b x min(-1), VO2 = 23.1 +/- 3.3ml x kg(-1) x min(-1), Woxy = 482.8 +/- 69.0 J x kg(-1) x min(-1), and Wmec 275.5 +/- 57.0 J x kg(-1) x min(-1) with mu'=0.57 +/- 0.09. In D HR (-9%), VE, VO2 and Woxy (-18%) were reduced when compared to A, decreasing mu' to 0.21 +/- 0.05. On the other hand mu' was found higher than 0.25 during A indicating an anaerobic contribution to energy expenditure; in D the mu' lower than 0.25 indicated a restoration of anaerobic energy sources. It might be proposed that a greater difference in mu' values between A and D also means a higher anaerobic energy contribution to the volleyball game.